Study to assess the association of PMS with sociodemographic factors and various coping behaviors adopted for premenstrual symptoms - Deepika Badkur; Suchita Singh; Vibha Arjaria; Arun Wanjpe (Asian Journal of Medical Sciences, 2023)
Background: Some women get through their monthly periods easily with few or no concerns. However, other women experience a host of physical and/or emotional symptoms just before and during menstruation (heavy bleeding and missed periods to unmanageable mood swings). These premenstrual syndrome (PMS) symptoms usually start to be problematic in the adolescent years and decline in the climacteric. Symptoms have a devastating effect which starts early in life. Aims and Objectives: The study was conducted to estimate the prevalence of PMS and its association with sociodemographic factors among female students of colleges situated in Ujjain city and coping behavior adopted to alleviate these symptoms. Materials and Methods: An observational follow-up study was conducted at 4 colleges selected by convenience sampling located in Ujjain city. PMS and menstrual profile-related data from 250 girls (18–25 years) who consented to participate were collected using a modified version of the Daily Record of Severity of Problems for at least 2 consecutive menstrual cycles. The diagnosis of PMS was made using the American College of Obstetrics and Gynecology criteria. Data analysis was done using SPSS version 16.0. Results: The prevalence of PMS was 39.6% and was not associated with any of the sociodemographic factors. It was found that majority of participants turned to healthy way of dealing with symptoms, i.e., taking hot or cold beverages and talking to family members. Conclusion: The frequency of PMS is relatively common in young girls, and most of the girls adopt home remedies to alleviate symptoms.